Anomalies Observed in VLF and LF Radio Signals on the Occasion of the Western Turkey Earthquake (Mw = 5.7) on May 19, 2011 - Biagi, F. (2013)
VLF radio signals lie in the 10 - 60 kHz frequency band. These radio signals are used for worldwide navigation support, time signals and for military purposes. They are propagated in the earth-ionosphere wave-guide mode along great circle propagation paths. So, their propaga-tion is strongly affected by the ionosphere conditions. LF signals lie in 150 - 300 kHz frequency band. They are used for long way broadcasting by the few (this type of broadcasting is going into disuse) transmitters located in the world. These radio signals are characterized by the ground wave and the sky wave propagation modes [1]. The first generates a stable signal that propagates in the channel Earth-troposphere and is affected by the surface ground and troposphere condition. The second instead gives rise to a signal which varies greatly between day and night, and between summer and winter, and which propagates using the lower ionosphere as a reflector; its propagation is mainly affected by the ionosphere condi-tion, particularly in the zone located in the middle of the transmitter-receiver path. The propagation of the VLF/LF radio signals is affected by different factors such as the meteorological condition, the solar bursts and the geo-magnetic activity. At the same time, variations of some parameters in the ground, in the atmosphere and in the ionosphere occurring during the preparatory phase of earthquakes can produce disturbances in the above men-tioned signals. As already reported by many previous studies [2-18] the disturbances are classified as anoma-lies and different methods of analysis as the residual dA/ dP [15], the terminator time TT [9], the Wavelet spectra and the Principal Component Analysis have been used [6,7]. Here the analysis carried out on LF and VLF radio signals using three different methods on the occasion of a strong earthquake occurred recently in Turkey is pre-sented.